KREATIVITAS GURU- GURU DI DESA TERPENCIL - Pera, Tri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This journal explains how the creativity of teachers in remote villages in SDN 25 Pulau Rimau in 1. carrying out tasks 2. providing motivation 3. teachers who are competent 4. building cooperative relationships internally and externally. This study used a qualitative approach with the types of cases in several teachers in 25 Rimau Islands Banyuasin District. The research subjects were: school principals, teachers, and parents of students [school committee]. The data collection uses observation and interviews. This study found the implementation of teacher teachers in 1. how a teacher has a role in carrying out his duties 2. can motivate participants students in accepting lessons by giving encouragement 3. can become teachers who have competence by using basic capital of a professional teacher 4. can work together both internally and externally to be built through relationships with students, with superiors, with fellow teachers, with the surrounding environment.